Development of Kidung Jula-Juli as a media for children's literacy - M. Gita Primaniarta; Heru Subrata (Universitas PGRI Madiun, 2022)
Kidung Jula-Juli is known as a sustainable art in East Java which has its own uniqueness. This uniqueness becomes a cultural value to be introduced to students. Kidungan Jula-Juli is a song development reseach with good messages from local wisdom. This research was conducted with a qualitative type of R&D (Research and Development) from the use of the ADDIE flow which has 5 steps (analyst, design, development, implementation, evaluation). Data collection techniques were obtained from the needs of observations and questionnaires The results of the research material show that experts accumulated a score of 5 while linguists formed a score of 4,386. Questionnaire responses from teachers and students were conducted by two schools consisting of 2 classes, each involving 4 teachers and 139 students. From 13 assessed aspects, it is safe to indicate that media literacy is very good. Kidung Jula-Juli which was developed as a literacy media is a media that can fill literacy strengthening activities in elementary school environmental.